Anomalous diffusion - Pirnat, Anja (Matrika, 2020)
Many processes in nature have been observed to deviate from normal diffusion. Their mean squared displacement grows either sublinearly or superlinearly in time. Such phenomena is called anomalous diffusion. As a model of ordinary diffusion random walk is presented. Then the generalization to continuous time random walk is made. In this model long waiting times and long jumps can be included and thus make a continuous time random walk suitable model to describe anomalous diffusion. Lastly, two examples of anomalous: sub- and super-diffusion are presented.
Keywords: diffusion; difuzija; model naključnega sprehoda; random walk; subdiffusion; subdifuzija; superdiffusion; superdifuzija